Design and Control of Swerve Drive Mechanism for Autonomous Mobile Robot - Haniff, Muhammad; Saputra, Hendri Maja; Zaki Hamidi, Eki Ahmad; Baskoro, Catur Hilman A.H.B.; Pratama, Saip Ardo (2022 16th International Conference on Telecommunication Systems, Services, and Applications (TSSA), 2022)
Mobile robots are robots with mobility capabilities, the ability of mobile robots is generally used for logistics purposes such as transporting goods. Steering mechanism is one of popular research subject from the development of mobile robot. Mobile robot steering mechanisms have been widely developed such as mecanum and omni-wheel steering which have a high maneuverability rate, but have a low traction value. Swerve steering is a steering mechanism that has advantages in terms of high maneuverability with traction values on a good track. This study discusses the design of a swerve steering module for mobile robot steering system. Swerve steering has the characteristic to perform translational movements and rotational movements at one point. Fuzzy logic control is designed for rotational movements performed with angle inputs, with a test of setpoint values from 5°-90° with an interval of every 5°, based on tests found the diferrence angle between actual and setpoint angle varies at value 0°-0.06°, with a first angular rise time of 1537 ms and an interval of rise time increase against an angle increase of 200 ms - 500 ms. Fuzzy logic control also designed for translational movement, carried out by input the distance to travel, based on tests with distance setpoints of 100 cm, 200 cm, 300 cm, 400 cm, and 500 cm, found the accuracy values of the distance traveled are 99.3 % ,99.72 % , 99.86%, 99.93%, 99.972%.